Morphogenesis of Cell-Shaped Assemblies via Heterotypic Assembly of Cyclic Triblock Peptides - Kim, Hyoseok; Ko, Sooho; Park, Keunwan; Lim, Yong-beom (John Wiley & Sons Ltd., 2022)
Despite the high prevalence and functional significance of nonregular assemblies in biology, little attention has been given to realize them in artificial systems. Here, the discovery of general principles underlying the formation of nonregular objects is described by chemical self-assembly. The cell-shaped assemblies (CSAs) are characterized by a main body comprising a nonregular vesicle and dendritically shaped spiky projections. The major mechanisms of CSA morphogenesis are: first, polycrystalline structures consisting of grains and grain boundaries induce the formation of nonregular objects by promoting nonuniform supramolecular crystal growth. Second, the fibrous nanostructures in 2D networks and in 1D bundles firmly support the main body and the spiky projections, respectively. This study also shows that there exist certain connections among entirely disparate entities, that is, organic supramolecular assemblies, inorganic materials, and cells regarding their fundamental principles of building block organizations. The principle behind the CSA formation can be applied to control the dynamic and mechanical properties of self-assembled materials.